A novel IGBT open-circuit protection method for three-phase PWM rectifier. (28th January 2020) - Yuan, Quande; Kou, Lei; Zhou, Jianing; Pi, Yuzhen; Ke, Wende
In order to avoid the damage or the secondary fault caused by serious over-current, a new solution for protection of IGBT open-circuit faults in three-phase PWM rectifier is presented in this paper. Firstly, the open-circuit faults features of three-phase PWM rectifier have been analysed, and it was found that the most obvious features of open-circuit faults in three-phase PWM rectifier are the rise of some phase currents and the drop of DC voltage. Secondly, compared with the maximum and minimum absolute values of phase currents under normal state, one of them always can be 1.3 times larger than that of normal state when open-circuit faults occur in IGBTs except all IGBTs. Finally, by observing the DC voltage and the currents' behaviour, the maximum-minimum values-based method can detect the open-circuit faults of the system. The experiment results have verified that the method can effectively detect the open-circuit faults in IGBTs and protect the system.